Control Panel for Transport Vehicle of Technological Purpose with Electric Traction - A. V. Schenyatskiy; R. S. Muzafarov; E. R. Muzafarov; E. S. Chukhlantsev; A. N. Dombrachev (Наука и техника, 2019)
The proposed design solution refers to elements of land vehicle bodies and namely to control panels of a power truck and it can be used to control vehicles of technological purpose with electric traction, as well as their hinged and trailed equipment. A technical problem of a device coinciding with the positive result from its application is to provide a possibility for controlling hinged or trailed equipment of a transport vehicle of technological purpose with the help of a panel. The control panel has a steering wheel located on its left side mounted on a steering column, a speedometer and a section of vehicle control devices, and there is a control unit for hinged and trailed equipment of the vehicle in the right part of the panel; it is made in the form of a box and there is a group of indicating devices, keypad and two function keys on the outer box surface. The group of indicating instruments includes a line of seven-segment indicators, a text LCD-indicator, a graphic TFT-display, the first and second LEDs indicating the status of hinged and trailed equipment. Indicating devices, keypad and two function keys are electrically connected to the control unit located inside the box. The control unit is based on an industrial microcontroller equipped with a non-volatile memory unit and a USART module connected via an interface converter unit to a radio module.